2012
DOI: 10.1523/jneurosci.0857-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Organization of Cerebral Projections to Identified Cerebellar Zones in the Posterior Cerebellum of the Rat

Abstract: The cerebrocerebellar connection makes use of two of the largest fiber tracts in the mammalian brain, i.e., the cerebral and medial cerebellar peduncles. Neuroanatomical approaches aimed to elucidate the organization of this important connection have been hindered by its multisynaptic nature, the complex organization of its components, and the dependency of conventional tracers on precisely placed injections. To overcome these problems, we used rabies virus (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
128
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(144 citation statements)
references
References 66 publications
(116 reference statements)
15
128
1
Order By: Relevance
“…The somatotopical organization of the corticoponto-cerebellar pathways from hindlimb, forelimb and face sensorimotor areas, their caudo-rostral arrangement in the pontine nuclei and their termination in the copula, the paramedian lobule, and the crus 2, more recently were confirmed by Odeh et al (2005) and, using retrograde transneuronal tracing, by Suzuki et al (2012).…”
Section: Pontine Nucleimentioning
confidence: 82%
See 1 more Smart Citation
“…The somatotopical organization of the corticoponto-cerebellar pathways from hindlimb, forelimb and face sensorimotor areas, their caudo-rostral arrangement in the pontine nuclei and their termination in the copula, the paramedian lobule, and the crus 2, more recently were confirmed by Odeh et al (2005) and, using retrograde transneuronal tracing, by Suzuki et al (2012).…”
Section: Pontine Nucleimentioning
confidence: 82%
“…Its hemisphere, the copula receives a projection from a more restricted ventral region of the caudal pons (blue, levels 6-8). This region corresponds with the projection of the hindlimb sensorimotor cortex (also see Suzuki et al, 2012). The paramedian lobule receives pontine input from more dorsal and rostral regions (levels 2-8) that were found to receive input from the forelimb sensorimotor cortex).…”
Section: Pontine Nucleimentioning
confidence: 85%
“…Both areas thus form a closed connectivity loop. However, recent research has qualified this interpretation and has shown that cerebro-cerebellar connectivity may be more open-ended, whereby the cerebellum receives inputs from multiple functional cerebral areas, including orbitofrontal areas from contra-and ipsilateral hemispheres (Suzuki et al, 2012). Human research exploring structural connectivity using diffusion imaging confirmed that cerebral fiber tracts connect predominantly to contralateral cerebellar areas, although they also show important ipsilateral connections (Salmi et al, 2010;Sokolov et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A similar conjunction might underlie H-reflex conditioning. The mossy fibers could convey efference-copy activity that reflects current CST influence over the H-reflex arc (Leergaard et al 2006;Ruigrok et al 2015;Suzuki et al 2012). The climbing fibers could indicate whether a reward occurs (e.g., whether the IO receives cortical input that reflects the click of the pellet dispenser or the taste of the food pellet) (see Ruigrok et al 2015 for review of IO inputs).…”
Section: Discussionmentioning
confidence: 99%